An MHD stagnation slip flow on a moving plate. - Md.Ali, Fadzilah; Nazar, Roslinda; Md. Arifin, Norihan; Pop, Ioan (IOP Science, 2011)
In this paper, the problem of a steady laminar boundary layer flow of a an electrically conducting fluid in the presence of a magnetic field near the stagnation point with slip on a moving plate is studied. The transformed boundary layer equations are solved numerically using the shooting method. Numerical results are obtained for various values of the magnetic parameter M and the slip factor λ. The skin friction coefficients and the velocity profiles f'(η), g(η) and h(η) for various values of M and λ are obtained and discussed.